Cost-Effectiveness of Operative Versus Nonoperative Management of Patients With Intra-articular Calcaneal Fractures. Issue 7 (July 2020) - Albin, Stephanie R.; Bellows, Brandon K.; Van Boerum, Drew H.; Hunter, Stephen; Koppenhaver, Shane L.; Nelson, Richard E.; Marcus, Robin; Dibble, Lee; Cornwall, Mark; Fritz, Julie M.
Abstract : Objective: To assess the costs, health gains, and cost-effectiveness of operative versus nonoperative treatment of calcaneal fractures over a 5-year time horizon from both US societal and payer perspectives. Methods: The societal perspective analysis included both direct medical costs and costs for missed work, whereas the health care payer perspective analysis included only direct medical costs associated with treatment and complications. A decision tree simulation model was developed to estimate the direct medical and indirect costs (2018 US$) and quality-adjusted life-years (QALYs) for treatment of patients sustaining intra-articular calcaneal fractures fixed with an extensile lateral approach. Direct medical costs were obtained from a large US health care system in Utah, Intermountain Healthcare, and indirect costs from the literature. Utility and probability parameters were also derived from the literature. Parameter uncertainty was explored using both one-way and probabilistic sensitivity analysis. Results: From a US societal perspective, operative treatment costs less ($35, 110 vs. $39, 870) and yielded more QALYs (3.89 vs. 3.51) over 5 years compared with nonoperative treatment. At a willingness-to-pay threshold of $50, 000 per QALY, operative fixation had an 89% probability of being cost-effective. From a health care payer perspective, operative management remained cost-effective as the incremental cost-effectiveness ratio is below the willingness-to-pay threshold of $50, 000/QALY. Conclusion: From both US societal and health care payer perspectives, operative treatment of displaced intra-articular calcaneal fractures utilizing an extensile lateral approach is cost-effective at commonly accepted willingness-to-pay thresholds compared with nonoperative treatment over a 5-year time horizon. Patient variability may impact cost-effectiveness and should be explored in future research. Level of Evidence: Economic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.